2019
DOI: 10.1111/emip.12280
|View full text |Cite
|
Sign up to set email alerts
|

Construct Equivalence of PISA Reading Comprehension Measured With Paper‐Based and Computer‐Based Assessments

Abstract: For many years, reading comprehension in the Programme for International Student Assessment (PISA) was measured via paper‐based assessment (PBA). In the 2015 cycle, computer‐based assessment (CBA) was introduced, raising the question of whether central equivalence criteria required for a valid interpretation of the results are fulfilled. As an extension of the PISA 2012 main study in Germany, a random subsample of two intact PISA reading clusters, either computerized or paper‐based, was assessed using a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
2
10
0
1
Order By: Relevance
“…It is important to emphasize that these items were absolutely invariant in the sense that they had the same item loadings and item intercepts, but average ability differences were not controlled for. Our findings, as well as other results in the literature (Jerrim et al, 2018a;Kroehne et al, 2019a), indicate that a small mode effect favoring the PBA mode remains for these invariant items and that this mode effect has the potential to distort reliable trends at the level of all participating countries in PISA. It could be the case that the identification of invariant items based on non-significance for the difference of item parameters caused the remaining mode effect.…”
Section: How Can Paper-based and Computer-based Tests Be Linked?supporting
confidence: 81%
See 2 more Smart Citations
“…It is important to emphasize that these items were absolutely invariant in the sense that they had the same item loadings and item intercepts, but average ability differences were not controlled for. Our findings, as well as other results in the literature (Jerrim et al, 2018a;Kroehne et al, 2019a), indicate that a small mode effect favoring the PBA mode remains for these invariant items and that this mode effect has the potential to distort reliable trends at the level of all participating countries in PISA. It could be the case that the identification of invariant items based on non-significance for the difference of item parameters caused the remaining mode effect.…”
Section: How Can Paper-based and Computer-based Tests Be Linked?supporting
confidence: 81%
“…Hence, differences in test performance can be attributed to differences in mode (CBA vs. PBA). The analysis of the field test data of all participating countries showed that in a 2PL model, the item discrimination between modes varied only slightly, but there were mode effects with regard to item difficulties (OECD, 2017; see also Kroehne et al, 2019a). Overall, the CBA items proved to be more difficult.…”
Section: Change In the Mode Of Test Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests were more difficult when presented on a computer (as compared to paper). Nevertheless, overall the transition from paper to computer does not seem to lead to pronounced changes in test results (e.g., Kroehne, Buerger et al, 2019 ; Schroeders & Wilhelm, 2011 ).…”
Section: Mode-effects and Measurement Biasmentioning
confidence: 99%
“…The ubiquity of the internet allows people to retrieve information and generate knowledge anytime and everywhere. This has led not only to changes in the modality of reading sources from paper-based to computerbased (e.g., Singer and Alexander, 2017;Kroehne et al, 2019), but increasingly requires readers to be able to integrate and evaluate information from different sources (List and Alexander, 2017a) due to the accessibility and multitude of available information. This competence, known as multiple document comprehension (MDC; e.g., Bråten and Strømsø, 2010a), entails the successful understanding, representation and integration of information from texts on the same subject matter stemming from different sources (also referred to as multiple documents).…”
Section: Introductionmentioning
confidence: 99%